Caracterização batimétrica e fisicooceanográfica do canal de acesso ao porto de Cabedelo/PB: uma análise ambiental ao derrame de óleo - Frazão, Luciana de Sousa (2011)
The State of Paraíba is one of the most dynamic states of Brazil, strategically located in the northeast, is notable for the excellent potential for integration of different transportation modes forming the states of Rio Grande do Norte, Pernambuco and Alagoas. The dynamic that occurs with port activity causes changes in the space where it is installed. And the elements of this space are always more than suffering direct or indirect influences as the flow in the port is expanded. Therefore, this region became subject to the accidental spillage of oil, because it presents a heavy traffic of ships of various sizes that can run aground or collide with oil causing accidental events. The study of geomorphological and sedimentological compositions of seafloor becomes important as more is known about the relationships between these parameters and associated fauna, and can identify their preferred habitats. The database background, acoustically collected along the proposed study area, is a wealth of information, which were duly examined, cataloged and made available. Such information can serve as an important tool, providing a geomorphological survey of the sedimentary area studied, and come to subsidize, in a flexible, future decision making. With the study area Port of Cabedelo, Paraíba - Brazil, this research aimed to evaluate the influence of the tidal surface and background in modeling the seabed, including the acquisition of information about the location of submerged rocky bodies and the depth of these bodies may turn out to be natural traps for the trapping of oil in case of leaks, and obtain the relationship between types of bed and the hydrodynamic conditions present in the region. In this context, for this study were collected bathymetric data (depth) and physical oceanographic (height of water column, water temperature, intensity and direction of currents, waves and turbidity), meteorological (rainfall, air temperature, humidity, winds and barometric pressure) of the access channel to the Port of Cabedelo / PB and its basin evolution (where the cruise ships dock), and includes tools of remote sensing (Landsat 7 ETM +, 2001), so that images and the results are integrated into Geographic Information Systems and used in the elaboration of measures aimed at environmental protection areas under the influence of this scale facilities, serving as a grant to prepare a contingency plan in case of oil spills in the region. The main findings highlight the techniques of using hydroacoustic data acquisition together bathymetric surveys of high and low frequency. From there, five were prepared in bathymetric pattern of Directorate of Hydrography and Navigation - DHN, with the depth in meters, on a scale of 1:2500 (Channel and Basin Evolution of Access to Port of Cabedelo), where there is a large extent possible beachrocks that hinder the movement of vessels in the port area, which can cause collisions, running aground and leaking oil. From the scatter diagram of the vectors of currents, it can be seen as the tidal stream and undergoes a channeling effect caused by the bidirectional effect of the tide (ebb and flood) in the basin of the Port of Cabedelo evolution in NW-direction SE and the highest speed of the currents occurs at low tide. The characterization weather for the period from 28/02 to 04/07/2010 values was within the expected average for the region of study. The multidisciplinary integration of products (digital maps and remote sensing images), proved to be efficient for the characterization of underwater geomorphological study area, reaching the aim to discriminate and enhance submerged structures, previously not visible in the images